Deaf’s Awareness on Sexual Abuse at The Vinh Long Deaf Club, Vietnam - Thi Thu Trang, Nguyen (Indonesian Social Work Consortium (ISWC), 2024)
Over the years, the deaf community in Vinh Long province has had to confront issues of harassment and sexual abuse due to their disabilities. Unfortunately, the majority of the deaf population lacks full awareness of harassment and sexual abuse, often misunderstanding behaviors such as teasing and unwanted touching as not constituting to sexual harassment. Therefore, by using qualitative and quantitative methods, this study aims to explore the current state of awareness about sexual abuse among the deaf in Vĩnh Long City. Simultaneously, the study intends to figure out the factors influencing the awareness of sexual abuse among the deaf and possible solutions for this issue. This article focuses on analyzing some key results from the research, especially the awareness of the deaf community in Vinh Long province on sexual harassment. Many victims knew that sexual harassment is illegal, but they accepted this behavior without reacting to it.